SEJARAH PERKEMBANGAN TAFSIR PADA ZAMAN RASULULLAH SAW, SAHABAT DAN TABIIN - Zainol, Nur Zainatul Nadra; Abdul Majid, Latifah (Journal of Techno-Social, 2012)
Al-Quran is the word of Allah was revealed to the Prophet Muhammad through Jibril AS. Appearances ‘ilmu Tafsir’ is the position of al-Quran as the primary source of Islamic law. The importance of studying the interpretation of the Quran is very high so it is difficult to understand the language, thus requiring the interpretation of Rasulullah saw, sahabat, tabiin and ulama. This knowledge also to understand the meanings of the Quran with more complete and accurate and can be picked up and passed a law contained therein. Thus, preventing a person from understanding the sentence the wrong way or deviate from its true meaning. This article aims to explain the history of the interpretation on the three days of the beginning of the time of the Rasulullah saw, sahabat and tabiin. The results showed that the interpretation of the rapid development has occurred in the day’s tabiin and have a tendency israilliyyat history